Respon Tanaman Sawi Hijau (Brassica juncea L.) dan Status Hara Nitrogen Tanah Terhadap Pemberian Pupuk Kandang dan Phonska Pada Berbagai Dosis - Djibril, Teungku Ahmad; Mulyati, Mulyati; Sukartono, Sukartono (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This research aims to determine the response of green mustard plants (Brassica juncea L.) to the application of cattle manure and phonska at various rates, and to determine Nitrogen status of the soils. The experiment was set up using a Completely Randomized Design (CRD) which consisted of 2 factors. The first factor was the application of 15:15:15 phonska with three doses, namely ; P1 = 100 kg/ha, P2 = 200 kg/ha, and P3 = 300 kg/ha. The second factor was cattle manure in 4 doses, namely ; K1 = 5 tons/ha, K2 = 10 tons/ha, K3 = 15 tons/ha, and K4 = 20 tons/ha. So that obtain 12 treatments. Each treatment was repeated 3 times, resulting in 36 experimental polybags. The results showed that the interaction of cattle manure and Phonska had influence on plant parameters, namely plant height at 28 days after planting, fresh and dry weight, and fresh weight of root, while on soil parameters, namely pH and C-Organic. The application of Phonska had a significant effect on plant parameters, namely plant height at 14 and 28 days after planting, number of leaves at 14, 21 and 28 days after planting, leaf area, fresh and dry weight, and fresh weight of root, while soil parameters such as soil pH and C-Organic. And cattle manure had a significant on soil parameters, namely pH and total soil N.